The regulation of MAP kinase signalling by dual-specificity protein phosphatases - Keyse, Steve M. (Henry Stewart Talks, 2011)
Signal transduction, Mechanisms of MAP kinase inactivation, Dual-specificity MAP kinase phosphatases, Fibroblast growth factor signalling